Método simplificado para cálculo e avaliação do uso combinado de técnicas compensatórias no manejo de águas pluviais em escala de loteamento - Peroni, Carolina Sulzbach Lima (2023)
The increase in impacts resulting from soil sealing and the inefficiency of conventional urban drainage systems has been emphasizing with greater magnitude, the need to rethink the conventional urban planning implemented in a large part of Brazil. Several alternative approaches to conventional stormwater management are known and successfully applied internationally; and, at a national level, they are in the (slow) process of being incorporated into the technical environment. The use of Detention Basins - BD to control and/or avoid new flooding points, in Brazilian cities of different sizes, is an increasingly common practice that demonstrates efforts to minimize such impacts, as well as reinforce the inefficiency of the existing infrastructure for current climatic and urban conditions. In view of this context of increasing advances in the adoption of these measures, the present study seeks to demonstrate, based on the proposition and application of a Simplified Method of Calculation and Evaluation of the combined use of CT (aailable at the link: https://drive.google.com/drive/folders/18zHM ObhFsCdC8Y6rbsf7RxWcP6lzP0c0?usp=drive_link), that the temporary storage and/or infiltration must be studied/planned from the lot scale, with the use of existing public areas in the allotment, called Lowered Green Areas - AVR. For this, four simulation arrangements were defined, namely: (1) without AVR; (2) with AVR in lots; (3) with AVR in public areas; and (4) with AVR on lots and public areas. This set of arrangements were simulated in three study areas, with different land use and occupation, but all with Detention Basins. The adopted parameter of comparison was the reduction of the dimensions of the BD, due to the distribution of AVR upstream. The simulations were carried out and, as expected, there was a reduction in the volumes of detention, and it was even possible to discard this unit, in some cases. The lag of peak times depended on the dimensions of the AVR (subject to change by the user), varying according to the rainfall adopted. These results proved to be positive for the implementation of storage and infiltration structures at different scales, but emphasizing that all these combinations influenced the reduction of the surface runoff volume and the delay of the peak flow; having little influence on the absolute value of the latter for the post-occupancy condition. The analysis of the hydrological behavior, through the entry and exit hydrographs of the BD, made it possible to identify that in addition to the hydrological benefits, it is essential to define other possible non-hydrological aspects for choosing the best arrangement. Finally, it was demonstrated that the development of a simplified method of calculating and evaluating compensatory techniques constitutes an instrument that can greatly facilitate the study of the use of these techniques, in an isolated or combined way, expanding their possibilities, but also identifying its limitations.